INVOLUTE CURVES OF BIHARMONIC CURVES IN SL2(R) - Korpinar, Talat; Asil, Vedat; Turhan, Essin (Editura Bibliotheca-Bibliotheca Publ House, 2011)
In this paper, we study involute curves of biharmonic curves in the SL2(R). Finally, we find out their explicit parametric equations.
Keywords: Biharmonic curve; SL2(R); curvature; torsion